Quand l'environnement devient support de formation - Loïc Braida; Michel Vidal (Éducation et Socialisation)
This article presents the results of a study to assess the impact of an educational strategy on youth (16-19 years) expectations of personal efficacy. Through open air physical activity and with support to the management and the expression of emotional skills, it aims the development of youth motivation, self-esteem and empowerment. The analysis of the evolution of the expectations of personal efficacy at different step of the device is an indicator wich show the changing attitudes of participants device above the challenges they face, their perseverance, and the management of their stress and anxiety. This paper proposes an intelligibility relationships model between environment, youth's emotional skills and youth's behavior.